(untitled) - Lewis, Richard J. (New York, 2002)
Hazardous Chemicals Desk Reference contains Safety Profiles, synonyms, physical properties, standards, and recommendations of government agencies for approximately 5,000 chemicals deemed both important and potentially hazardous by the international scientific community. Substances were chosen on the basis of meeting a variety of criteria
Keywords: Hazardous substances,Các chất độc hại